Studi Pendahuluan Pengembangan Aplikasi Augmented Reality Untuk Transliterasi Aksara Jawa Cetak - Widiarti, Anastasia Rita (Universitas Multi Data Palembang, 2024)
The Javanese script as an Indonesian cultural asset must be preserved and disseminated to the current generation so that it is not increasingly lost from memory. Augmented reality (AR) technology has the opportunity to be used in developing interesting applications, because the nature of the technology that combines the real world with the virtual world can attract young people to use it in their daily lives. The chosen AR development method is the Multimedia Development Life Cycle method, and the software tools used are Unity and Vuforia. As a first step, a collection of marker images has been carried out from the segmentation results of the Hamong Tani manuscript on page 2. From the test results on Javanese script objects, it was found that the AR application functions properly and correctly on Javanese script images with the smallest size of 2x2 cm, and the largest at 11x11 cm. For the smallest font size, the distance from the camera to the Javanese script is a minimum of 5 cm and a maximum of 9 cm, while for the largest font size, the distance is a minimum of 18 cm and a maximum of 46 cm.